2016
DOI: 10.18632/oncotarget.9677
|View full text |Cite
|
Sign up to set email alerts
|

β2-spectrin depletion impairs DNA damage repair

Abstract: β2-Spectrin (β2SP/SPTBN1, gene SPTBN1) is a key TGF-β/SMAD3/4 adaptor and transcriptional cofactor that regulates TGF-β signaling and can contribute to liver cancer development. Here we report that cells deficient in β2-Spectrin (β2SP) are moderately sensitive to ionizing radiation (IR) and extremely sensitive to agents that cause interstrand cross-links (ICLs) or replication stress. In response to treatment with IR or ICL agents (formaldehyde, cisplatin, camptothecin, mitomycin), β2SP deficient cells displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 64 publications
(90 reference statements)
0
32
0
Order By: Relevance
“…6C). To determine whether the decrease in RPA and Rad51 focus formation in MCL-1-depleted cells postirradiation was due to decreased ssDNA production as a result of defective resection, we did a quantitative resection assay using the ER-AsiSI system (23). In this resection assay system, MRE11-depleted cells were used as a positive control for loss of resection.…”
Section: Mcl-1 In Dna Damage Repair Molecular and Cellular Biologymentioning
confidence: 99%
“…6C). To determine whether the decrease in RPA and Rad51 focus formation in MCL-1-depleted cells postirradiation was due to decreased ssDNA production as a result of defective resection, we did a quantitative resection assay using the ER-AsiSI system (23). In this resection assay system, MRE11-depleted cells were used as a positive control for loss of resection.…”
Section: Mcl-1 In Dna Damage Repair Molecular and Cellular Biologymentioning
confidence: 99%
“…αII Sp functions together with the DNA ICL repair proteins XPF and FANCA to localize at nuclear foci after DNA ICL damage [ 16 , 18 , 20 ]. A recent report has shown β2 spectrin deficiency disturbs chromosome stability [ 21 ], and a number of studies have shown that spectrin is an essential regulator in a variety of cancers [ 22 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…for 30 mins before stalling with 2mM Hydroxy Urea (HU) for 2h,then washed in PBS for 2 times, incubated in medium containing with 450 mM Iodoxy Uridine (IdU) for 1hr Horikoshi et al, 2016).…”
Section: Dna Replication Restart Assay and Fork Protection Assaymentioning
confidence: 99%